An Analysis of Self-regulated Learning in Student Speaking Skill - Nikyta Olivia Edini Putri; Sulastri Manurung; Adam Adam (South Sulawesi Education Development (SSED), 2025)
Self-regulated learning (SRL) refers to the process by which individuals take control of their own learning. self regulated learning involves forethought phase, performance/ volitional control and self reflection. determining the planning stage in learning speaking, monitoring the process of learning speaking and evaluating what else needs to be improved in speaking. The aims of this study is to analyze how students regulate themselves in speaking learning. Digging deeper into how self-regulated is applied in students and what strategies they do. This study used qualitative methods and Semi-structured interviews by asking 10 vocational high school students. Only 10 students were taken because the study used purposive sampling technique, a technique where researchers deliberately select samples based on the objectives to be achieved, obtaining information from students who have relevant speaking learning experience to answer research questions. The data collection is using audio recordings and the data is processed using thematic analysis. After the interview, the results of the students' answers will be described one by one, coding the data, providing data categories, analyzing the data and developing conclusions from all answers. The results showed that students were better at organizing themselves in the forethought phase. Students have appropriate planning strategies for speaking learning. From the results and discussion that have been described, self-regulated learning is very important in students' speaking learning. It is important for teachers to provide training on how to self-regulate in speaking learning. Provide efficient directions and strategies according to each student's ability.